THE ROLE OF CYTOKINES IN IMMUNOPATHOGENESIS OF ACUTE PANTHEATITIS (review article) (Modern education and development, 2024)
AP is an aseptic inflammation of the demarcation type, which is based on necrosis of the acinar cells of the pancreas and enzymatic aggression with subsequent expanding necrosis and dystrophy of the gland, in which damage to surrounding tissues and distant organs, as well as systems and the addition of a secondary purulent infection is possible ( 15). To date, acute pancreatitis remains one of the most pressing problems in abdominal emergency surgery ( 1) .